THE ANALYSIS OF SPATIAL FORM AND ITS RELATION TO GEOGRAPHIC THEORY. - King, Leslie J. (Annals of the Association of American Geographers)
An interest in the relations between geography and geometry has been a continuing theme in geographic studies. A review of current research which is consistent with this theme reveals a greater emphasis now on the mathematics of spatial patterns and the properties of the geometries which are assumed. A challenge for geography is to combine this interest in geometries with the work on human behavior over space and to develop process theories from which the spatial patterns can be deduced.